Magnetic and Electrical Properties of Leachate - Kartika Kirana; Nurul Naufa; Estevanus Huliselan; Satria Bijaksana (Institute for Research and Community Services (LPPM) ITB, 2011)
Heavy metals content as well as magnetic and electrical properties of leachate from Sarimukti, West Java were studied in an attempt to seek correlation between heavy metals content and magnetic/electrical properties. Such correlation is expected to open the way for the use of magnetic/electrical properties as proxy indicators for the concentration of heavy metals in the leachate. The number of leachate samples studied is 21; 15 were taken spatially at depth of 1 m while the remaining 6 samples were taken vertically at a particular point. Measurement results showed that the heavy metals content in the leachate has a smaller concentration, except for Fe. The correlation between magnetic susceptibility and heavy metals content was found to be not so significant. The best correlation coefficient between magnetic susceptibility with heavy metals in leachate was found in Zn. Correlation between electrical conductivity and heavy metal is also not so significant, except for Zn and Cd. The use of magnetic properties as proxy indicator for heavy metals content in leachate is plausible provided that the magnetic susceptibility exceeds certain threshold value. Correlation between magnetic susceptibility, electrical conductivity and heavy metal content would be good if each quantity has a large value.